2017
DOI: 10.1126/sciadv.1701508
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast direct electron transfer at organic semiconductor and metal interfaces

Abstract: Conformation-specific direct interfacial electron transfer is observed by the first ultrafast electric field–induced VSFG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 71 publications
(135 reference statements)
5
54
0
8
Order By: Relevance
“…This is consistent with our experimental results, where we found that the initial band gap of P3HT is 2.1 eV and by depositing P3HT on Au, we create an interfacial gap of 1.5 eV. 14 We further evaluate the level of hybridization by calculating the real space wavefunction along the material. Using the DFT calculated wave function data which includes the lattice points in the reciprocal space and their corresponding plane wave coefficients, real- space wavefunctions were constructed.…”
supporting
confidence: 90%
“…This is consistent with our experimental results, where we found that the initial band gap of P3HT is 2.1 eV and by depositing P3HT on Au, we create an interfacial gap of 1.5 eV. 14 We further evaluate the level of hybridization by calculating the real space wavefunction along the material. Using the DFT calculated wave function data which includes the lattice points in the reciprocal space and their corresponding plane wave coefficients, real- space wavefunctions were constructed.…”
supporting
confidence: 90%
“…The frequency transition stabilizes in a very rapid period (turn‐on time less than 20 s), which is mainly determined by two factors: fluid‐infusing time and optoelectronic conversion delay (turn‐on time). [ 27,28,36,37 ] The hydrophilic treatment could greatly reduce the fluid‐infusing time to few seconds, while the turn‐on time is a tradeoff between the flexibility of the thin film and light sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…2c displays the SFG spectrum obtained for the palmitic acid monolayer on the NaCl subphase in a condensed aqueous phase. The SFG setup used for this experiment has been described in Xiang, Li et al 30 SFG spectroscopy is interface sensitive and has been previously employed to study atmospherically relevant systems at air/water interfaces. 31 35 The ssp-polarized SFG spectrum in Fig.…”
Section: Resultsmentioning
confidence: 99%